Surface and Catalytic Properties of NiO–FeO Solids Supported on AlO - G.A. El-Shobaky; A.M. Ghozza; N.M. Deraz (Adsorption Science & Technology)
A series of NiO–Fe 2 O 3 catalysts supported on γ-Al 2 O 3 was prepared. The effect of the NiO and Fe 2 O 3 contents and the precalcination temperature on the surface and catalytic properties of the various solids has been investigated. The surface characteristics, viz. SBET, V p and r, were determined using N 2 adsorption conducted at –196°C. The catalytic activities of the various solids were studied using the oxidation of CO by O 2 at temperatures in the range between 150°C and 400°C. The prepared solids were preheated in air at various temperatures between 400°C and 1000°C. The results obtained revealed that the SBET values of the different solids decrease progressively on increasing the precalcination temperature above 400°C due to sintering. The specific surface areas were also found to decrease on increasing both the NiO and Fe 2 O 3 contents. The catalytic activities, expressed as reaction rate constant (k) and reaction rate constant per unit area (k), were found to decrease on increasing the precalcination temperature in the range 400–1000°C. Furthermore, the amounts of NiO and Fe 2 O 3 in the different solids modified their catalytic activities in different manners.